High Density Thickening and Gravity Transportation of Cuajone Tailings - Figueroa, JH; Roman, J (Paste 2009: Twelfth International Seminar on Paste and Thickened Tailings, 2009)
The mineral processing industry is facing more than ever restrictions in water availability; the lack of water resources is making to consider alternative processes, which lead to efficient water consumption operations. Such is the case of Southern Copper Corporation which is considering thickening technologies to recover water from the Cuajone tailings to assure the water requirements for its expansion projects. A pilot campaign was completed to investigate the feasibility of recovering water from the tailings. The tests were completed with the collaboration of three world leading companies in thickening technologies, and the results show that it is feasible to recover water from the Cuajone tailings to a rate of 315 litres/s and that the de-watered slurry can flow by gravity through the existing open channel systems.